Obowiązki równego traktowania ubiegających się o zamówienia publiczne - Kowalczyk, Ewaryst (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The book describes the meaning of the obligations of equal treatment of applicants for public procurement under Polish legislation. The two main research goals include: analysis of normative sources regarding the obligations of equal treatment in public procurement and the scientific and dogmatic characteristics of these obligations. Resolving the indicated problems requires clarification of many detailed issues.
Keywords: zamówienia publiczne; równe traktowanie; zasada równości; obowiązki